Angiographic Findings in Patients Presented with Inferior Wall Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention - Iqbal, Waseem; Ikramullah; Khan, Muhammad Azam; Kamal, Atif; Khan, Roman; Khan, Tilawat (Indus Journal of Bioscience Research, 2025)
Background: Inferior wall myocardial infarction is a prevalent subtype of acute myocardial infarction, often associated with variable coronary artery involvement. Angiographic evaluation remains a critical tool for identifying the culprit vessel and guiding revascularization strategies. Objective: To determine the frequency of angiographic findings in patients presented with inferior wall myocardial infarction. Study Design: Cross-sectional study. Duration and Place of Study: The study was conducted from January to May 2025 at the Department of Cardiology, Lady Reading Hospital, Peshawar. Methodology: A total of 131 patients aged 18–75 years presenting with inferior wall myocardial infarction and undergoing coronary angiography within 24 hours were enrolled. Patients with advanced comorbidities, cardiogenic shock, or contraindications to angiography were excluded. Demographic and clinical data including age, gender, body mass index, socioeconomic status, and residential background were recorded. Coronary arteries were classified as diseased when 50% or greater luminal narrowing was observed. Results: The mean age was 53.01±9.03 years, and most patients were male (77.1%). Left anterior descending artery involvement was observed in 53.4%, left circumflex artery in 24.4%, and right coronary artery in 46.6% of cases. Significant associations were found between left anterior descending artery disease and both age (p=0.003) and socioeconomic status (p<0.001). Left circumflex artery involvement was significantly associated with age (p=0.018). Conclusion: Coronary angiography in inferior wall myocardial infarction revealed notable variability in arterial involvement, with age and socioeconomic status influencing disease distribution.